Determinan Nilai Perusahaan Industri Manufaktur Di Indonesia - Putri, Ferica Christinawati; Nainggolan, Yohanna Thresia (Politeknik Negeri Ambon, 2024)
Thel objelctilvel of thils study ils to ildelntilfy and elxamilnel thel varilablels that ilmpact thel valuatilon of companilels opelratilng iln thel food and belvelragel ilndustry and lilsteld on thel Ilndonelsila Stock Elxchangel. Thel varilablels elxamilneld iln thils study arel thel silzel of thel company, thel lelvelragel (melasureld by thel delbt to elquilty ratilo), and thel ratel of corporatel growth. Thils study elmploys a causal-associlatilvel relselarch approach by utillilsilng selcondary data. Thel samplel for thils study consilsts of 16 food and belvelragel filrms that welrel lilsteld on thel Ilndonelsila Stock Elxchangel beltweleln 2017 and 2021. Thel samplilng approach elmployeld was purposilvel-samplilng, elncompassilng a total of 80 obselrvatilons. Thel data undelrwelnt procelssilng through thel utillilsatilon of thel multilplel lilnelar relgrelssilon statilstilcal telst melthod utillilsilng Statilstilcal Packagel for thel Socilal Scilelncels (SPSS) softwarel. Thel filndilngs of thils study delmonstratel that thel factors of filrm silzel, lelvelragel (delbt to elquilty ratilo), and filrm growth collelctilvelly ilmpact filrm valuel. Partilally, company silzel, lelvelragel (delbt to elquilty ratilo), and company growth ilnfluelncel company valuel. Selvelral basilc thilngs dilffelrelntilatel thils relselarch from prelvilous relselarch, ilncludilng thel varilablels useld, thel relselarch populatilon, and thel yelar of thel relselarch. Ilt ils hopeld that thils relselarch can bel useld as consildelratilon iln makilng delcilsilons about ilnvelstilng iln thel Ilndonelsilan Stock Elxchangel. Futurel relselarch nelelds to consildelr a broadelr samplel.